Work and "Mass Personal" Communication as Means of Navigating Nutrition and Exercise Concerns in an Online Cancer Community - Love, Brad; M. Thompson, Charee; Crook, Brittani; Donovan-Kicken, Erin (JMIR Publications, 2013)
BackgroundHealth and psychosocial outcomes for young adults affected by cancer have improved only minimally in decades, partially due to a lack of relevant support and information. Given significant unmet needs involving nutrition and exercise, it is important to understand how this audience handles information about food and fitness in managing their cancer experiences. ObjectiveUsing the theory of illness trajectories as a framework, we explored how four lines of work associated with living with a chronic illness such as cancer (illness, everyday life, biographical, and the recently explicated construct of communication work) impacts and is impacted by nutrition and exercise concerns. MethodsFollowing a search to extract all nutrition- and exercise-related content from the prior 3 years (January 2008 to February 2011), a sample of more than 1000 posts from an online support community for young adults affected by cancer were qualitatively analyzed employing iterative, constant comparison techniques. Sensitized by illness trajectory research and related concepts, 3 coders worked over 4 months to examine the English-language, de-identified text files of content. ResultsAn analysis of discussion board threads in an online community for young adults dealing with cancer shows that nutrition and exercise needs affect the young adults' illness trajectories, including their management of illness, everyday life, biographical, and communication work. Furthermore, this paper helps validate development of the "communication work" variable, explores the "mass personal" interplay of mediated and interpersonal communication channels, and expands illness trajectory work to a younger demographic than investigated in prior research. ConclusionsApplying the valuable concepts of illness, everyday life, biographical, and communication work provides a more nuanced understanding of how young adults affected by cancer handle exercise and nutrition needs. This knowledge can help provide support and interventional guidance for the well-documented psychosocial challenges particular to this demographic as they manage the adversities inherent in a young adult cancer diagnosis. The research also helps explain how these young adults meet communication needs in a "mass personal" way that employs multiple communication channels to meet goals and thus might be more effectively reached in a digital world.